2006
DOI: 10.1152/ajpheart.00223.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic reperfusion of the ischemic heart and oxygen radical generation

Abstract: Postischemic myocardial contractile dysfunction is in part mediated by the burst of reactive oxygen species (ROS), which occurs with the reintroduction of oxygen. We hypothesized that tissue oxygen tension modulates this ROS burst at reperfusion. After 20 min of global ischemia, isolated rat hearts were reperfused with temperature-controlled (37.4°C) Krebs-Henseleit buffer saturated with one of three different O2 concentrations (95, 20, or 2%) for the first 5 min of reperfusion and then changed to 95% O 2. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 35 publications
3
60
1
1
Order By: Relevance
“…Gradual thrombolytic reperfusion could therefore lead to higher ROS production. Indeed, Angelos [25] recently reported that in isolated rat hearts the highest level of ROS is produced following reperfusion at the lowest blood oxygen saturation. However, there is a lack of clinical or experimental data comparing ROS production following thrombolytic reperfusion and PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Gradual thrombolytic reperfusion could therefore lead to higher ROS production. Indeed, Angelos [25] recently reported that in isolated rat hearts the highest level of ROS is produced following reperfusion at the lowest blood oxygen saturation. However, there is a lack of clinical or experimental data comparing ROS production following thrombolytic reperfusion and PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the VEGF expression, observed in the infarct region of SM-treated hearts, could explain the higher capillary density and vessel formation. It is likely that the newly formed vessels might improve tissue perfusion in and around the ischemic zone, resulting in increased blood flow and myocardial PO 2 . Several studies have demonstrated that expression of certain growth factors, including VEGF, by the transplanted cells is a possible mechanism for functional improvement in the heart (19,25,34).…”
Section: Discussionmentioning
confidence: 99%
“…The particulate probes measure PO 2 in the tissue milieu. Lithium octa-n-butoxy-substituted naphthalocyanine radical (LiNc-BuO) is a particulate oximetry spin probe that we have recently synthesized and validated for in vivo oximetry (2,15,27,42,43). The LiNc-BuO crystals are composed of stacks of neutral radicals of lithiated naphthalocyanine macrocycles (28).…”
mentioning
confidence: 99%
“…Recently, we noted a paradoxical ROS response at the onset of reperfusion when O 2 concentration was varied (2). The burst of ROS at the onset of reperfusion was significantly increased under hypoxic reperfusion conditions in the isolated perfused heart, compared with reperfusion with 95% O 2 saturated buffer.…”
mentioning
confidence: 96%